Photoeffect Peculiarities in Macroporous Silicon Structures - L. A. Karachevtseva; V. F. Onyshchenko; A. V. Sachenko (Хімія, фізика та технологія поверхні, 2010)
The effects of increase in photoconductivity in the macroporous silicon structures have been examined as a function of the distance between cylinder macropores. The ratio of macroporous silicon photoconductivity to bulk silicon one has been found to achieve a maximum at the distance between macropores equal to the double thickness of the Shottky layer what corresponds to the experimental results. The relaxation time of photoconductivity for macroporous silicon structures was found to be defined by the light modulation of the barrier on macropore surfaces whereas its relaxation to occur according to the logarithmic law. If T>180 K, the temperature dependence of the relaxation time of photoconductivity is defined by a thermo-emission mechanism of the current transport in the space charge region and below 100 K the relaxation time is controlled by the processes of tunnel current flow.